In Search of Quality Students: Animation Media to Improve Students’ Critical Thinking Skills - Suari, Susy; Indrawadi, Junaidi (Indonesian Research Journal in Education |IRJE|, 2024)
This research aimed to determine the effect of animated videos on the essential thinking skills of students at one junior public-school students in West Sumatera. It used a quantitative pre-experimental method using the one-group pretest and post-test design to determine the effect of animated video media. The results showed that animated videos could make students think critically based on the descriptive results. In addition, it was found that animated videos were effective for material on natural resources in Indonesia. It can be seen from the data normality test, which states that the data is usually distributed if azymp > 0.05. The t-test analysis results illustrate the effect of using animated video media on improving the critical thinking skills of one junior public-school students in West Sumatera. Thus, animated videos can improve students' critical thinking processes. Therefore, the application of animated videos in learning at school is good, valid, and effective because it can enhance students' critical thinking processes.